Short Synthesis of Dopamine Agonist Rotigotine - Shekhar, Chandra; Karmakar, Santanu; Mainkar, Prathama S.; Chandrasekhar, Srivari (Synthesis, 2024)
A practical and short synthesis of FDA approved drug, Rotigotine, is achieved in two steps from 5-methoxy-2-tetralone, which in turn was synthesised by [4+2] cycloaddition of the in situ generated methoxyaryne from its precursor aryl triflate with benzyloxybutadiene or from 4-methoxyindanone via ring expansion using trimethylsilyldiazomethane.
Keywords: CNS; dopamine; rotigotine; tetralone; aryne; cycloaddition; reductive amination